PENGARUH MOTIVASI INTRINSIK TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN TRASFORMASIONAL DAN BUDAYA ORGANISASIONAL (STUDI PADA GURU SD NEGERI KECAMATAN DORO KABUPATEN PEKALONGAN) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to know how influence intrinsic motivation on teacher performance, how influence transformational leadhership influence on teacher performance, how influence culturerole organizational influence on teacher performance, how influence transformational leadhership moderation intrinsic motivation impact on teacher performance, and how influence culture roleorganizational moderation pedagogic competence impact on teacher performance. In this study population on Teacher in Doro Subdistrict Regency Pekalongan, while the samples used as many142 people as respondents to the random sampling proportional technique. Data were analyzed using multiple regression analysis. Results of the study can be summarized as follows intrinsicmotivation influence on teacher performance, transformational leadership not influence on teacher performance, culture role organizational significant positif influence on teacherperformance, transformational leadership not moderation intrinsic motivation impact on teacher performance, and culture role organizational not moderation intrinsic motivation impact onteacher performance. Keywords: Intrinsic Motivation, Transformational Leadership, Culture Role Organizational, and Teacher Performance.